The Russian Myth of Power versus Personality Cult - Kowalska, Martyna (Poznańskie Studia Slawistyczne, 2013)
The considerations in this paper focus upon the Russian idea of which consequence and extension is mythology of the Soviet times. We refer to the myths of tsarist Russia and to a specific relation to the authorities in Russia. The main theme of this paper concerns mythology of the Soviet times, especially one of its elements namely, the myth of power. The attention has been shifted to the history of personality cult, which revolved around Joseph Stalin. The position of the leader in the Stalinist soviet state can be conditioned by a relation to the authorities of which origin may be traced back to pre-revolutionary times. In the summary, an attempt has been made to unmask the myth of the leader on the basis of selected works from the circle of Russian samizdat literature.